(4R)‐ and (4S)‐Fluoroproline in the Conserved cis‐Prolyl Peptide Bond of the Thioredoxin Fold: Tertiary Structure Context Dictates Ring Puckering. Issue 9 (27th May 2013) - Rubini, Marina; Schärer, Martin A.; Capitani, Guido; Glockshuber, Rudi
<x xml:space="preserve">Abstract</x> Fine‐tuning protein stability: The non‐natural amino acids (2S, 4R)‐ and (2S, 4S)‐fluoroproline modulate protein stability by biasing the proline ring pucker and the cis/trans equilibrium of prolyl peptide bonds. We incorporated both fluoroproline stereoisomers at the invariant cis‐proline residue of the thioredoxin fold. The results show that tertiary structure context overrules the conformational preferences of fluoroprolines.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>